IMPACT OF FUNGICIDES ON POWDERY MILDEW, ALTERNARIA AND CERCOSPORA LEAF SPOT DISEASES OF NIGER (GUIZOTIA ABYSSINICA CASS) CV UNDER SOUTH GUJARAT REGION - PRASHANT B. SANDIPAN; P. K. JAGTAP; M. C. PATEL (The Bioscan, 2014)
Niger (Guizotia abyssinica Cass) is one of the important minor oilseed crop of hilly regions globally it is used for oil purpose. Not much information is available on diseases of Niger crop plant. Therefore a study was planned to document the diseases with four replications at the Niger Research Station (NRS) at Navsari Agricultural University (NAU), Vanarasi, Navsari and Gujarat on the foliar diseases of Niger cultivar. In this experiment, six different fungicides have been evaluated to control the Powdery mildew, Cercospora and Alternaria leaf spot diseases out of which, all the fungicidal treatments were significantly superior over the control. The least intensity of Cercospora and Alternaria leaf spot 12.42 PDI and 14.39 PDI was observed respectively in T6 (Carbendazim + Mancozeb 0.2%), which was followed by treatment T1 (Carbendazim 0.1%) for Cercospora (14.42 PDI) and Alternaria leaf spot (17.01 PDI). Whereas, the least intensity of Powdery mildew disease 6.05 PDI was observed in T5 (Wettable sulphur 0.2%), which was followed by T1 (Carbendazim 0.1%) 7.52 PDI. In respect to seed yield analysis, treatment T6 (Carbendazim + Mancozeb 0.2%) gave significantly higher yield followed by treatment T1 (Carbendazim 0.1%). Therefore it may be concluded that Carbendazim + Mancozeb 0.2% fungicide is superior for the control of the leaf spot diseases and gave higher seed yield in Niger crop.